Pengaruh Kualitas Produk, Harga, dan Citra Merek terhadap Keputusan Pembelian Kulkas Sharp di Lotte Grosir Semarang - Sesilia Via Naya Suntoro; Ida Martini Alriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of product quality, price, and brand image on the purchase decision of Sharp Refrigerator at Lotte Grosir Semarang. The research method used a quantitative approach with an accidental sampling technique on 95 respondents who were consumers of Sharp Refrigerators. The research instrument was in the form of a questionnaire, while data analysis was carried out by multiple linear regression using the SPSS program. The results of the hypothesis test showed that product quality had a positive and significant effect on the purchase decision, with a calculated t value of 2. 474 greater than the table t of 1. 986 and a significance of 0. 015 < 0. 05. The price variable also has a positive and significant effect on the purchase decision, as shown by the t-value calculated as 1. 939 with a significance of 0. 005 < 0. 05. Furthermore, brand image was proven to have a positive and significant effect on purchase decisions, with a calculated t value of 3. 057 greater than the t table of 1. 986 and a significance of 0. 003 < 0. 05. Overall, the findings of this study confirm that product quality, price, and brand image are important factors that influence consumers' decisions to buy Sharp Refrigerators at Lotte Grosir Semarang. The implications of this research emphasize the need for companies to maintain product quality, set competitive prices, and strengthen brand image to increase consumer appeal.